A Crude Shock : Explaining the Impact of the 2014-16 Oil Price Decline Across Exporters - Grigoli, Francesco; Herman, Alexander; Swiston, Andrew (Washington, D.C. : International Monetary Fund, 2017)
The decline in oil prices in 2014-16 was one of the sharpest in history, and put to test the resilience of oil exporters. We examine the degree to which economic fundamentals entering the oil price decline explain the impact on economic growth across oil exporting economies, and derive policy implications as to what factors help to mitigate the negative effects. We find that pre-existing fundamentals account for about half of the cross-country variation in the impact of the shock. Oil exporters that weathered the shock better tended to have a stronger fiscal position, higher foreign currency liquidity buffers, a more diversified export base, a history of price stability, and a more flexible exchange rate regime. Within this group of countries, the impact of the shock is not found to be related to the size of oil exports, or the share of oil in fiscal revenue or economic activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet